ASPEK PSIKOLOGIS PESERTA DIDIK: KEBERAGAMAN DAN PENGARUHNYA PADA PEMBELAJARAN - Jihan Amelia Putri; Nurfarida Deliani; Juliana Batubara (LPPM STAI Muhammadiyah Probolinggo, 2026)
The diversity of psychological aspects of students, such as intelligence, emotions, creativity, motivation, attention, memory, language, talent, personality, and learning styles, plays a very significant role in the learning process. This article aims to comprehensively examine how these various psychological aspects influence the dynamics of learning and the final results achieved by students. Through a qualitative research approach with a literature study, this research systematically identifies the various psychological characteristics that cause differences in learning styles, patterns of interaction in the classroom, and responses to various teaching methods applied by teachers. The results of the study show that a deep understanding of these psychological diversities can help educators develop learning strategies that are more adaptive, effective, and tailored to the individual needs of students. Thus, these strategies can increase activity, motivation, and overall learning achievement. In addition, this article emphasizes the importance of applying individual and differentiated approaches in the learning process. Learning planning to optimally accommodate the unique needs of each student. This approach not only helps meet the unique needs of students, but also creates an inclusive, supportive, and conducive learning environment for balanced psychological well-being. The practical implications of these findings are directed at balancing learning models that are responsive to psychological aspects, which in turn can improve the quality of interaction between teachers and students and improve educational outcomes in a holistic, sustainable manner that has a positive impact on the overall development of students